An investigation of methods for remote bottom and subbottom marine sediment classification using a chirp sonar - Claassen, Daniel Marthinus (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Ing.) -- University of Stellenbosch, 1992.